Imaging photo-induced dynamics in halomethane molecules with coincident ion momentum spectroscopy - Kaderiya, Balram (Kansas State University, 2021)
Molecular transformations triggered by the absorption of light are of tremendous importance in our day-to-day life, science, and technology. Examples of such "photo-induced" reactions include, among many others, photosynthesis, solar energy conversion, and mechanisms behind human vision. Besides knowing the final outcome of such reactions, for many scientific and technological applications it is crucially important to understand how they evolve in time, and how the motion of individual atoms leads to a certain outcome. For decades, resolving these processes in time represented a severe experimental challenge since the atomic motion involved is extremely fast. The availability of ultrashort, femtosecond laser pulses in combination with novel molecular imaging techniques provides experimental tools needed to address this challenge. This thesis describes the application of coincident ion momentum imaging setup, sometimes called "a reaction microscope", for studies of photo-induced dynamics in halomethane molecules (CH₂I₂, CH₂ICl, CH₃I). The main objective of this work is to visualize light-induced breaking, rearrangement and formation of molecular bonds, and to determine relevant mechanisms and time scales. Halomethanes are often considered as model systems for studying such prototypical photochemical events because they are small enough to allow for reasonable electronic structure calculations and for coincidence detection of all molecular fragments, while being large enough to be of chemical relevance and to undergo some fundamental chemical transformations. The work described here covers three different regimes of light-molecule interaction: (1) ionization and fragmentation by an intense near-infrared (NIR) field, (2) excitation of a neutral molecule by a single ultraviolet (UV) photon; and (3) ionization and fragmentation by a single extreme ultraviolet (XUV) photon. We specifically focus on several aspects of halomethane photochemistry that are of general importance, have been actively discussed in literature, and yet are difficult to access using more established imaging or spectroscopic techniques. More specifically, we first characterize molecular response to a single intense femtosecond NIR pulse at 800 nm, identifying and disentangling different ionization and fragmentation channels, and their signatures in various coincident observables. Then we apply multiple ionization and rapid dissociation ("Coulomb explosion") by such a pulse as a tool to map molecular dynamics in pump-probe experiments. In this approach, the information on molecular geometry at the time when the probe pulse arrives is extracted from the coincident measurement of the 3D momentum vectors of the detected fragment ions. We start with the NIR pump / NIR probe experiments on CH₂I₂ and CH₂ICl molecules, aimed at characterizing bound and dissociating wave packets induced by a strong NIR field. Here, we find that both, dissociation dynamics and molecular halogen elimination (I₂ or ICl) are mainly governed by the large-scale bending vibrations of the molecule, even though (weak) signatures of stretching vibrations can be also observed in the spectra. Focusing on the I₂ (or ICl) elimination channel, which requires breaking two carbon-halogen bonds and formation of a new bond between the two halogen atoms, we demonstrate how it can be disentangled from the other fragmentation channels, and find that it is dominated by a direct, "synchronous" pathway. Then we apply the same approach and the same NIR probe pulses to study the photoexcitation of diiodomethane (CH₂I₂) by a femtosecond UV pulse at 266 nm in a UV pump / NIR probe experiment. Here, in addition to two-body dissociation and I₂ elimination channels, we also observe a significant contribution of three-body dissociation. This channel can be easily separated in our triple-coincidence measurements, but is notoriously difficult to identify with most of the other techniques. Besides that, we find signatures of transient CH₂I-I isomer formation within the first 100 femtoseconds after the initial photoexcitation. While the picosecond-scale isomerization of CH₂I₂ was clearly demonstrated earlier in the liquid-phase experiments in solution, and was shown to occur due to the interaction with the solvent, the existence of a much faster, intra-molecular isomerization pathway for isolated molecules in a gas phase was debated in literature. In this work, we provide direct evidence of such ultrafast, sub-100 fs CH₂I₂ isomerization, and demonstrate that the decay of this short-lived isomer opens up an additional pathway for molecular iodine elimination. Finally, we have performed a complementary study on CH₂ICl and CH₃I molecules employing short extreme ultraviolet pulses (XUV) from FLASH II free-electron laser facility in Hamburg, Germany. Here, one femtosecond XUV pulse at ~ 53 nm central wavelength is used to initiate the dynamics, mainly by single-photon ionization, while the second identical pulse is used to probe the evolution of the created ionic-state wave packets. Employing the same ion momentum imaging setup, we map different dissociative ionization channels and observe signature of intramolecular electron transfer between different sites of a dissociating molecular ion. In contrast to the results of earlier FEL experiments on X-ray inner-shell photoionization of dissociating halomethanes, which could be readily explained using the classical over-the-barrier charge transfer model, our data for valence XUV ionization suggest a more subtle dependence of the charge transfer probability on the internuclear distance, likely determined by the delocalization of molecular orbitals. Overall, the work presented in this thesis advances our understanding of different pathways in strong-field and single-photon induced photochemistry of halomethanes, and demonstrates an efficient and visual approach for mapping transient reaction intermediates. The tools and methodology presented here can be applied to study a broad range of ultrafast photochemical reactions, and can be useful for many strong-field imaging and control applications.
Keywords: Ultrafast lasers; Molecular dynamics; Photochemistry; Strong fields; Momentum spectroscopy